DO YOU LIKE LISTENING TO MUSIC?: STUDENTS’ THOUGHT ON THEIR VOCABULARY MASTERY USING ENGLISH SONGS - Shaleha Isnaini; Dyah Aminatun (Journal of English Language Teaching and Learning, 2021)
Many EFL students are still having difficulties in learning vocabulary. It is because most of English vocabulary are different in term of written and spoken. To face this facts, EFL students have their way to learn and add their new English words There are many ways to enhance students’ vocabulary mastery. One of the ways is through English songs. This research aims to find out students’ thought on their vocabulary mastery using English songs. The researcher used descriptive qualitative study as the research design. The subjects of this research were the 30 students from English Education study program of Faculty of Arts and Education in Universitas Teknokrat Indonesia. Data were collected through questionnaire and interview. From the result of the questionnaire and the interview, it revealed that English songs have strong influence on their English skill. Also, the students think that English songs help them learn new vocabulary, unfamiliar vocabulary, how to pronounce the word correctly. Thus, finally, they can improve their English vocabulary.